Impact of Tax Knowledge, Tax Rates, Tax Payment Methods, Tax Sanctions on Taxpayer Compliance LevelsMicro Small and Medium Enterprises - Asri Ady Bakri (Penelitian dan Pengembangan Ilmu, 2024)
The objective of this inquiry is to evaluate the impact of tax knowledge, tax rates, tax payment mechanisms, and tax sanctions on compliance among MSME taxpayers in Sumenep, Madura. The X variables consist of tax knowledge, tax rates, tax payment mechanisms and tax penalties. The Y variable is Micro Small and Medium Enterprises taxpayer compliance. The population consists of MSME taxpayers. The sampling technique used simple random sampling, and 132 sources were obtained. The data used is primary data taken using a questionnaire. This research uses a multiple linear analysis method processed with SPSS 24. The results of this research show that partially tax knowledge has a significant impact of 0.047. Tax rates have a significant effect of 0.000, tax payment mechanisms have a significant effect of 0.002 and tax penalties have a significant effect of 0.023. Meanwhile, simultaneously tax knowledge, tax rates, tax payment mechanisms, tax sanctions have a significant impact on taxpayer compliance of 0.000.